(untitled) (Vietnam Journal of Agriculture and Environment, 2023)
Rice (Oryza sativa) has been regarded as one of the most important food crops that plays an important role in the socio-economic development of Vietnam. Ensuring food security and promoting sustainable rice production and export are two crucial tasks. This report provides an implementation result of the National Rice Product development project up to the year 2020 and anorientation of product research and development to 2030. Particularly, a total of 11 and five new high-grade rice varieties and promising lines have been constructed, respectively. Among them, eight rice varieties, including ĐH12, OM429, BĐR27, GL516, OM375, OM20, OM08, and HD11, were transferred to enterprises and developed in various ecological regions. Furthermore, advanced cultivation practices have been constructed for the Northern provinces, the Red River Delta, the North and South Central regions, and the Mekong River Delta. Certified seeds, registered seeds and basis seeds, together with advanced production models, were developed in many provinces to ensure the production of high-grade rice varieties in Vietnam. Finally, the results of this project offer an opportunity to cooperate with enterprises to promote and replicate the production of newly developed rice varieties and produce rice seeds.